Payments Arrangements and the Expansion of Trade in Eastern and Southern Africa - Eken, Sena (Occasional Papers; Occasional Paper, 1982)
In late 1979, the African Center for Monetary Studies requested, on behalf of the Association of African Central Banks (AACB), that the Fund staff prepare a study describing the existing payments, exchange control, and exchange rate arrangements in the proposed 17-nation Preferential Trade Area (PTA) of Eastern and Southern African States, analyzing any payments obstacles to trade in the region, and recommending improvements in payments arrangements that would promote intraregional trade.